GAMBARAN PENGETAHUAN IBU TENTANG KONSUMSI SUMBER CASEIN, GLUTEIN DAN SUPLEMEN PADA ANAK AUTIS DI YAYASAN PEMBINAAN ANAK CACAT (YPAC) MEDAN TAHUN 2015 - Dewita Wiliandia Sari; Ernawati Nasution; Jumirah . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2016)
The increase in the number of autism children throughout the world, including in Indonesia, needs serious attention in handling it. Autism can be recovered by early intervention, that is, by paying attention to providing food for autism children which cannot be separated from women’s behavior in providing food for autism children. The research used descriptive method with cross sectional design which was aimed to find out the description of women’s knowledge and the consumption of the source of casein, gluten, and supplement for autism children at fondation coaching disabled children (YPAC) Medan in 2015. The population was all women who had autism-school children and were under autism therapy at fondation coaching disabled children (YPAC) Medan and 25 of them were used as the samples. The data were gathered from the data of women’s knowledge and the data of consuming the source of casein, gluten, and supplement, by conducting interviews and questionnaires. The result of the research showed that women’s knowledge of consuming the source of casein, gluten, and supplement for autism children was in good category (56%). The consumption of the source of casein and gluten, for autism children was in bad category (80% and 70%), and the consumption of supplement for autism children was in bad category (80%). It is recommended that at fondation coaching disabled children (YPAC) increase counseling for parents, especially women about the consumption of the source of casein, gluten, and supplement for autism children. Parents should increase their knowledge of the need for nutrition in autism children so that they can give good food to their autism children. Keywords: Women’s Knowledge, Casein, Gluten, Supplement, Autism Children